2017
DOI: 10.3389/fmicb.2017.01708
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Influence of Segmented Filamentous Bacteria on Transcriptomic Response of Gnotobiotic Mice Exposed to TCDD

Abstract: Environmental toxicants such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), an aryl hydrocarbon receptor (AhR), are known to induce host toxicity and structural shifts in the gut microbiota. Key bacterial populations with similar or opposing functional responses to AhR ligand exposure may potentially help regulate expression of genes associated with immune dysfunction. To examine this question and the mechanisms for AhR ligand-induced bacterial shifts, C57BL/6 gnotobiotic mice were colonized with and without s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 82 publications
(99 reference statements)
1
13
1
Order By: Relevance
“…In addition, Stedtfeld et al reported that compared with levels under a traditional gut microbiome, 2,3,7,8-tetrachloro dibenzo- p -dioxin (TCDD, an AhR ligand) induced shifts in the abundances of SFB and Bacteroides fragilis (an immune suppressor) in mice. Moreover, the TCDD-induced host response was significantly regulated by the presence of SFB in the gut microbiome, demonstrating therapeutic potential between AhR ligands and key commensals [42]. Dysbiosis of the gut microbiota has been identified as a potential factor that causes autoimmune diseases, which in humans are attributed to multiple factors, even though the relative contribution of the gut microbiota remains elusive.…”
Section: The Gut Microbiota and Autoimmune Diseasesmentioning
confidence: 99%
“…In addition, Stedtfeld et al reported that compared with levels under a traditional gut microbiome, 2,3,7,8-tetrachloro dibenzo- p -dioxin (TCDD, an AhR ligand) induced shifts in the abundances of SFB and Bacteroides fragilis (an immune suppressor) in mice. Moreover, the TCDD-induced host response was significantly regulated by the presence of SFB in the gut microbiome, demonstrating therapeutic potential between AhR ligands and key commensals [42]. Dysbiosis of the gut microbiota has been identified as a potential factor that causes autoimmune diseases, which in humans are attributed to multiple factors, even though the relative contribution of the gut microbiota remains elusive.…”
Section: The Gut Microbiota and Autoimmune Diseasesmentioning
confidence: 99%
“…For this, the application of ‘humanized’ gnotobiotic animal model that harbors defined collection of sequenced microbial communities, has gained momentum in recent years in microbiome research ( Faith et al, 2010 ). This allows proof-of-mechanism study to examine the potential impacts of diet ( Turnbaugh et al, 2009b ), antibiotic, environmental toxicants ( Stedtfeld et al, 2017 ) and host genotypic variation ( Ley et al, 2005 ) on the microbiota and disease manifestation, due to changes in microbiota composition, transcriptomes, proteomes or metabolomes post-induced variations can be extracted and characterized to understand the operation of the microbiota. Besides, ‘humanized’ gnotobiotic mice can be used in preliminary testing of the therapeutic efficacy in treating dysbiosis-associated diseases, as they allow monitoring of the pharmacokinetic–pharmacodynamic changes in microbial communities, thus facilitating optimization of treatment and dosage regime ( Mahe et al, 1987 ; Silva et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, dioxin-elicited changes in the host decreased B . fragilis [41], which, in our study was relatively lower in abundance in the higher breastmilk toxicants exposure group, as were some Lactobacillus . Due to financial constraints, we only had measured levels of the less toxic of the dioxin-like PCBs; however, we expect these to be moderately correlated with dioxins and other more toxic dioxin-like compounds [3].…”
Section: Discussionmentioning
confidence: 55%